Sensory Evaluation and Physical Characteristics of Ice Cream with The Comparison of Soy Whey and Moringa Leaves Puree - I Gede Arie Mahendra Putra; Putu Trisna Maharani; Fauzan Maulana Yusuf; Made Karlinda Putri Kirana; Sang Ayu Putu Sollenne Abilita; I Wayan Mulya Adi Saputra (Warmadewa University Press, 2024)
Soy whey is one of the byproducts of tofu processing industry that has not been widely utilized until now, potentially causing environmental pollution. One of the efforts to manage tofu waste is to transform it into an innovative food product such as ice cream. However, this endeavor undoubtedly requires the addition of other ingredients to enhance the quality of the product's appearance, such as natural colorants, one of which is moringa leaves. Moringa leaves were rich in chlorophyll and other bioactive components, making them suitable for used as a natural colorant in the form of puree. This study aimed to determined the influence of the comparison between soy whey to moringa leaves puree on the sensory characteristics of ice cream and to obtained the appropriate formulation for the production of ice cream with the best sensory characteristics. The study used a Randomized Complete Block Design (RCBD) with treatments consisting of different comparison of soy whey and moringa leaves puree (10:90; 30:70; 50:50; 70:30; 90:10). The best sensory results will be followed by testing the physical characteristics of the ice cream. The research showed that the comparison of soy whey to moringa leaves puree (30:70) was the best treatment in terms of sensory characteristics for color (4.15), aroma (4.22), texture (4.48), taste (4.19), and overall acceptances (4.48) with a preference category of slightly liked, along with physical characteristics included 41.63% overrun, 53.8 minutes melting time, and color characteristics of L* 60.23; a* -7.4; b* 20.43 categorized as bitter green.